Modeling of a Public Utility Facility from Total BIM Data - Gardzińska, Anna (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The purpose of this work is to present the possibilities of using tacheometric measurement technology in the development of a 3D geometric model of an existing building and the directions of using BIM technology in the process of building operation. General information on the development of BIM technology was presented, and issues related to the construction of 3D models were discussed. Attention was also drawn to the need to update the information assigned to the model on an ongoing basis in order to effectively manage the building. Supplementing the model with metadata regarding the building materials used will allow for a precise and quick analysis of all renovation assumptions. The created 3D model can be used to control the condition of structures or in safety and risk management.
Keywords: tacheometric surveying; public utility facility; 3D model; BIM Model